Application of WebGIS in Managing and Monitoring Greenery in Schools: A Case Study at the Thu Dau Mot University - Le Tan Dat, Nguyen; Minh Hai, Tu (VNU Journal of Science: Earth and Environmental Sciences; Vol 40 No 4, 2024)
This research developed a WebGIS system for managing green spaces at the Thu Dau Mot University. The system utilizes PostgreSQL for data storage and GeoServer for spatial data sharing, enabling efficient communication of field data. The platform's user-friendly interface, combined with QGIS tools and PostGIS/PostgreSQL, allows for easy data visualization and management, even for users without GIS expertise. This cost-effective solution facilitates quick information sharing, fosters a shared understanding of the data, and enables more efficient and sustainable management of the university's green spaces.